Investigation of CO2 Extract of Portulaca oleracea for Antioxidant Activity from Raw Material Cultivated in Kazakhstan - Meruyert I. Tleubayeva; Raisa M. Abdullabekova; Ubaidilla М. Datkhayev; Margarita Yu. Ishmuratova; Mereke B. Alimzhanova; Kaldanay K. Kozhanova; Aida M. Seitaliyeva; Kairat S. Zhakipbekov; Zhanar B. Iskakova; Elmira A. Serikbayeva; Elena V. Flisyuk (International Journal of Biomaterials)
Medicinal plants remain as an important resource in the fight against many diseases, especially in developing countries. Antioxidants are substances capable of delaying, retarding, and preventing the oxidation of lipids or substances that delay or prevent free radical reactions during lipid oxidation. Natural antioxidants such as ascorbic acid, tocopherol, phenolic compounds, and flavonoids are a safe alternative to chemical antioxidants. In present work, results of antioxidant activity of raw materials from the cultivated plant Portulaca oleracea are presented. The extraction time was optimized to 780 minutes; the yield of extractive substances was 1.25% in the production of CO2 extract under subcritical conditions. For the first time, the antioxidant activity of Portulaca oleracea CO2 extract was determined by the amperometric method. Gas chromatography-mass spectrometry (GC-MS) chemical analysis of Portulaca oleracea CO2 extract dissolved in hexane revealed 37 components, including a complex mixture of aldehydes, alkanes, alkenes, esters, diterpenes, steroids, vitamin E, and carbohydrates. The investigation results showed that the Portulaca oleracea CO2 extract was promising for pharmaceutical, cosmetic, and food industries and had great potential for the prevention and treatment of diseases caused by oxidative stress.